2016
DOI: 10.1111/epi.13578
|View full text |Cite
|
Sign up to set email alerts
|

2‐Deoxy‐d‐glucose enhances tonic inhibition through the neurosteroid‐mediated activation of extrasynaptic GABAA receptors

Abstract: We demonstrated, for the first time, that 2-DG potentiates the extrasynaptic tonic GABAergic current through activation of neurosteroidogenesis. Such tonic inhibition represents the main conductance responsible for the antiseizure action of this glycolytic inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…A recent preliminary study reported that 2-DG reduces both spontaneous (and miniature) excitatory synaptic currents and spontane-ous inhibitory synaptic currents (Pan et al 2014), supporting this hypothesis. Also, a recent study in hippocampal dentate gyrus neurons showed that 2-DG enhanced tonic GABAergic current and reduced neuron excitability (Forte et al 2016). In addition, glycolytic inhibition may shift G-6-P into the pentose phosphate pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent preliminary study reported that 2-DG reduces both spontaneous (and miniature) excitatory synaptic currents and spontane-ous inhibitory synaptic currents (Pan et al 2014), supporting this hypothesis. Also, a recent study in hippocampal dentate gyrus neurons showed that 2-DG enhanced tonic GABAergic current and reduced neuron excitability (Forte et al 2016). In addition, glycolytic inhibition may shift G-6-P into the pentose phosphate pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus altering energy metabolism may represent a novel strategy and alternative therapy for seizure control, particularly for those resistant to drugs (Kawamura et al 2016). We and others previously proposed that direct inhibition of glycolysis leads to seizure control and that the glycolytic inhibitor 2-deoxy-D-glucose (2-DG) produces acute anticonvulsant effects in vitro (Forte et al 2016;Stafstrom et al 2009) and chronic antiepileptic effects in vivo (Garriga-Canut et al 2006;Gasior et al 2010;Stafstrom et al 2009). Specifically, we previously showed that 2-DG decreases epileptiform activity induced by elevated extracellular potassium, 4-aminopyridine (4-AP), and bicuculline in brain slices from adult animals (Stafstrom et al 2009).…”
mentioning
confidence: 99%
“…Elevated GABAergic activity leads to increased extracellular potassium, which supports hyperexcitability and epileptiform synchronization (Zuckermann and Glaser, 1968;Fertziger and Ranck, 1970;de Curtis and Gnatkovsky, 2009). On the other hand, there are studies suggesting that the impaired GABAergic inhibition, related to a selective loss of inhibitory interneurons, accounts for epileptiform activity (Wendling et al, 2002;Forte et al, 2016). Although electrophysiological validations are required, it is tempting to speculate that the normalization of GABAergic transmission by GDNF prevents the broad spatial hypersynchronous recruitment of neurons and interneurons observed at the transition from interictal to ictal activity (Schevon et al, 2012;Fujita et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…49 In addition to its effects on excitatory synaptic transmission, 2DG may also affect GABAergic signaling, specifically by potentiating extrasynaptic tonic GABAergic current through activation of neurosteroidogenesis. 53 However, unlike glutamate in excitatory neurotransmission, GABA does not couple inhibitory neuronal activity with glucose utilization. 54 Thus, although 2DG may increase postsynaptic tonic inhibition, this action appears independent of its effect on glycolysis.…”
Section: Potential Mechanisms Of 2dg Actionmentioning
confidence: 99%